Proceedings of the 7th International Conference on Knowledge Innovation and Invention, Volume 1: Proceedings of ICKII 2024, Volume 1 (Lecture Notes in Electrical Engineering; Engineering; Engineering (R0), 2026)
This volume represents the proceedings of the 7th International Conference on Knowledge Innovation and Invention 2024 (ICKII 2024). This conference is organized by IEEE Tainan Section Sensors Council, National Formosa University of Taiwan, and International Institute of Knowledge Innovation and Invention (IIKII), and held on August 16-18, 2024, in Nagoya, Aichi, Japan. The conference provided a unified communication platform for researchers in a range of topics, such as information technology, communication science & engineering, computer science, electrical & electronic engineering, automation engineering, big data computation, machine learning, and other engineering related fields. This proceedings volume enables interdisciplinary collaboration of science and engineering technologists in the academic and industrial fields, as well as networking internationally. This book is open access, which means that you have free and unlimited access